Kepemimpinan Kolaboratif dalam Momentum Pemilu 2024 Membangun Partisipasi Demokratis yang Berkelanjutan - Nurfadilla, Yunita; Nurdin, Ismail (Jurnal Pemerintahan dan Politik, 2024)
General elections (Pemilu) are a crucial democratic instrument for expressing the sovereignty of the people. Basic principles of elections, such as direct participation and fairness for all participants, reflect constitutional commitments to ensure a fair and transparent democratic process. Collaborative leadership is recognized as an approach that can strengthen the integrity and success of elections, enabling cooperation among various parties to achieve common goals. This research aims to explore the relationship between collaborative leadership and sustainable democracy in the 2024 elections in Indonesia. The method used in this research is literature study. The results of the discussion indicate that collaborative leadership plays an important role in encouraging active participation of the community, especially the younger generation, in elections. This leadership operates through cooperation among various election actors, including election organizers, political parties, and civil society, to achieve fair, transparent, and democratic elections. Sustainable democracy, on the other hand, supports elections by strengthening democratic institutions and promoting inclusive and transparent decision-making. Thus, it can be concluded that the integration of collaborative leadership and sustainable democracy is key to the success of the 2024 elections in Indonesia.